Geothermal Energy Resource Investigations at Mt. Spurr, Alaska - Turner, D. L.; Wescott, E. M. (University of Alaska Fairbanks. Geophysical Institute., 1986)
Spurr volcano is a composite Quaternary cone of largely andesitic composition located on the west side of Cook Inlet about 80 miles west of Anchorage and about 40 miles from the Beluga electrical transmission line. Geologic mapping (Plate 1-1) shows that the present summit depression was produced by a Mt. St. Helens-type sector collapse, rather than by a caldera collapse. Geochronologic and previous tephrachronologic studies show that there has been an active magmatic system at Spurr volcano during the late Pleistocene-to-Holocene time interval that is of critical interest for geothermal energy resource assessment. Major effort was devoted to geochemical and geophysical surveys of the accessible area south of Mt. Spurr, in addition to geologic mapping and geochronologic studies. Many coincident mercury and helium anomalies were found, suggesting the presence of geothermal systems at depth. Extremely large electrical self-potential anomalies were also found, together with extensive zones of low resistivity discovered by our controlled-source audiomagnetotelluric survey. The juxtaposition of all of these different types of anomalies at certain areas on the south slope of Crater Peak indicates the presence of a geothermal system which should be accessible by drilling to about 2000 ft depth. It is also evident that there is a strong volcanic hazard to be evaluated in considering any development on the south side of Mt. Spurr. This hazardous situation may require angle drilling of production wells from safer areas and placement of power generation facilities at a considerable distance from hazardous areas.